Python Programming Advanced : Understanding Weird Concepts - Sarda, Shubham (Packt Publishing, 2020)
Take your understanding of Python programming a step ahead by learning the advanced concepts About This Video Gain a solid understanding of Python's advanced concepts Unlock the exciting new features of Python 3.8 and 3.9 Grasp useful tips to apply your Python knowledge in the real-world In Detail Do you have basic knowledge of Python and want to explore more advanced concepts? This course will help you out. The course starts with the topic of recursion and explains its concepts, such as tracing tree, call stack, and tree recursion. Next, you will learn the role of lambda functions, map, filter, reduce, and comprehension in Python programming. Moving along, you will uncover why regular expressions are used and how decorators help in adding new functionality to an existing object. Next, you will understand logging and learn how to accomplish date and time tasks with the help of the date and time module. Towards the end, you will go through the latest features of Python 3.8 and Python 3.9, such as union operators, type hinting, and zone info. By the end of this course, you will be well-versed with the advanced topics of Python and will have gained the confidence to apply them in Python programming.